End-users personalization potentials and factors towards effective housing occupancy: Malaysian development perspective - Isa, A. A. (Asian Research Publishing Network, 2016)
This study investigated end-users personalization potentials and factors contributing to efficient housing occupancy that are embedded in the Housing Occupancy Model (HOM). These factors were sourced through literature review, policy documents along with experts' opinions till consensus was reached on five factors, which are: personalization, satisfaction, environmental condition, attitude towards occupancy and subjective norm to occupancy. Thereafter, an instrument based on Structural Equation Model (SEM) was designed and administered to a total of 247 respondents. Subsequently, the inter-relationships between and within these factors were tested and fully investigated towards developing a valid HOM. Therefore, the results obtained indicating that the probability (p-value) of Chi-square value is 0.011 for 'satisfaction' in the prediction of occupier intention is therefore supported. The value obtained for 'environmental condition' in the prediction of occupier intention is 0.242 which is above the supporting threshold range of 0.01-0.0985, hence is not supported. Sequentially, the value of 0.962 obtained for 'subjective norm to occupancy' in the prediction of occupier intention is highly out of range, whereas a value of 0.006 is supported for 'attitude towards occupancy' in the prediction of occupier intention. 'Personalization' in the prediction of occupier intention obtained a value of 0.012 which is thus significantly supported. 'Attitude towards occupancy' in the prediction of subjective norm to occupancy with value of 0.135 is not supported. However, < 0.001 value for 'personalization' in the prediction of satisfaction is highly significantly supported. The outcome of this HOM will help in effective public housing delivery and occupancy among the low and middle-income earners. In addition it will be beneficial to policy makers, academicians and professionals in arriving at sustainable housing decisions relating to occupancy issues in Malaysia and other developing economies.